2022
DOI: 10.1177/10497315221085014
|View full text |Cite
|
Sign up to set email alerts
|

Extended Case Management Services Among Resettled Refugees in the United States

Abstract: Purpose Economic self-sufficiency is the priority of U.S. refugee resettlement policy, and opportunities for economic integration are shaped by social service contexts. While reception and placement services are typically provided for 3–8 months, extended case management (ECM) involves 2 years of services. This study examines associations between economic integration outcomes—employment, income source, income, and employment satisfaction—and exposure to ECM. Method We compare 243 resettled refugees, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Several demographic factors were associated with employment such as age, health perception, household size, dependent children, and education. For instance, six studies found that older age is a constraint to employment [ 8 , 30 , 32 , 41 , 57 ]. One study reported that child-bearing age and parenthood at age 30 have a significant negative impact on employment [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several demographic factors were associated with employment such as age, health perception, household size, dependent children, and education. For instance, six studies found that older age is a constraint to employment [ 8 , 30 , 32 , 41 , 57 ]. One study reported that child-bearing age and parenthood at age 30 have a significant negative impact on employment [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The structure and characteristics of a family also wield substantial influence on the employment status of women with a refugee background. For instance, marital status was found to be a facilitator of employment among refugee women in Sweden because marital status can provide additional social and economic support, easing integration into the job market [ 32 , 35 ]. Conversely, having a larger household size was identified as an impediment to employment [ 57 ], while having more children posed significant barriers to employment [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations